(Chemical Composition of Indonesian Traditional Food Additives Which Possibly Containing Borax) - Surjati Herman, Atih; Iskandar, Renawati; Dwi Astuti, Binarti (Balai Besar Industri Agro, 1991)
Five types of traditional food additives collacted from markets in Java and Manado, namely